Employee Green Behavior on Generation X and Y Millennial - Mayangsari, Resti Eva; Nawangsari, Lenny C.; Sutawidjaya, Ahmad H. (International Review of Management and Marketing, 2021)
Employee Green Behavior (EGB), which is an important component of organizational sustainability. This study aims to analyze the effect of Green Recruitment, Green Training and Employee Green Behavior on Environment Performance in two groups of generation X and generation Y employees. The paradigm in this study is Positivism with the type quantitative research and using survey methods. The study population was employees at PT PT Wira Cipta Perkasa with a total sample of 100 people. The data analysis used was the Structural Equation Model with Smart PLS software. The results of the study prove that Green Recruitment and Green Training have an effect on Environment Performance through Employee Green Behavior in Generation X. Whereas in Generation Y Millennia it is proven that Green Recruitment has an effect on Environment Performance through Employee Green Behavior but Green Training has no effect. Keywords : Green Recruitment, Green Training, Employee Green Behavior, Environment Performance JEL Classifications: L2, J2 DOI: https://doi.org/10.32479/irmm.11633